tATAmI: A Platform for the Development and Deployment of Agent-based AmI Applications - Olaru, Andrei; Benea, Marius-Tudor; Seghrouchni, Amal El Fallah; Florea, Adina Magda (Procedia computer science, 2015)
In the vision of a future pervaded by Ambient Intelligence (AmI), innovative solutions are required in order to facilitate the development of applications able to fulfill the real needs of the users. In using agents for building AmI applications, there is a lack of platforms and languages that strike a good balance between flexibility and power of expression, on the one hand, and ease of use and quick deployment, on the other hand. We introduce the tATAmI platform, which together with the S-CLAIM AOP language presents a suitable solution for these issues. This paper presents the architecture of tATAmI together with a brief description of two scenarios that were implemented using the platform and some other important technical aspects concerning it.